Catatan Beberapa Jamur Makro Dari Taman Eden 100, Kawasan Toba, Sumatera Utara, Indonesia: Deskripsi dan Potensinya - Oktan Dwi Nurhayat; Ivan Permana Putra; Sita Heris Anita; Dede Heri Yuli Yanto (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: The record and research on macrofungi from Taman Eden 100, Toba-Samosir Regency, North Sumatra, Indonesia, was conducted to provide some information about their current status and potential use in the future. Methods: This research was divided into three steps: exploration, identification, and literature studies of the potential use from the identified macrofungi. Results: The research had successfully identified 14 macrofungi that were classified into 4 orders and 9 families. All the macrofungi found were Basidiomycota, namely Gymnopilus sp., Marasmiellus sp.1, Marasmiellus sp.2, Marasmius sp., Favolaschia sp., Coprinellus sp., Coprinopsis sp., Auricularia sp.1, Auricularia sp.2, Auricularia sp.3, Auricularia sp.4, Tylopilus sp., Suillus sp., and Russula sp. The identified macrofungi are potentially used as food supplements, medicine, bio-fertilisers, bioherbicides, and bioremediation agents based on the literature. Conclusions: Taman Eden 100 has a unique fungal diversity of macrofungi and has never been published in a scientific journal. Further investigations are needed to determine the fungal diversity and potential use of macrofungi in other places in Taman Eden 100.